Effect of early vs standard approach to tracheostomy on functional outcome at 6 months among patients with severe stroke receiving mechanical ventilation: the SETPOINT2 randomized clinical trial - Bösel, Julian; Niesen, Wolf-Dirk; Salih, Farid; Morris, Nicholas A.; Ragland, Jeremy T.; Gough, Bryan; Schneider, Hauke; Neumann, Jan-Oliver; Hwang, David Y.; Kantamneni, Phani; James, Michael L.; Freeman, William D.; et al. (The journal of the American Medical Association, 2022)
Many patients with severe stroke have impaired airway protective reflexes, resulting in prolonged invasive mechanical ventilation.To test whether early vs standard tracheostomy improved functional outcome among patients with stroke receiving mechanical ventilation.In this randomized clinical trial, 382 patients with severe acute ischemic or hemorrhagic stroke receiving invasive ventilation were randomly assigned (1:1) to early tracheostomy (≤5 days of intubation) or ongoing ventilator weaning with standard tracheostomy if needed from day 10. Patients were randomized between July 28, 2015, and January 24, 2020, at 26 US and German neurocritical care centers. The final date of follow-up was August 9, 2020.Patients were assigned to an early tracheostomy strategy (n = 188) or to a standard tracheostomy (control group) strategy (n = 194).The primary outcome was functional outcome at 6 months, based on the modified Rankin Scale score (range, 0 [best] to 6 [worst]) dichotomized to a score of 0 (no disability) to 4 (moderately severe disability) vs 5 (severe disability) or 6 (death).Among 382 patients randomized (median age, 59 years; 49.8% women), 366 (95.8%) completed the trial with available follow-up data on the primary outcome (177 patients [94.1%] in the early group; 189 patients [97.4%] in the standard group). A tracheostomy (predominantly percutaneously) was performed in 95.2% of the early tracheostomy group in a median of 4 days after intubation (IQR, 3-4 days) and in 67% of the control group in a median of 11 days after intubation (IQR, 10-12 days). The proportion without severe disability (modified Rankin Scale score, 0-4) at 6 months was not significantly different in the early tracheostomy vs the control group (43.5% vs 47.1%; difference, −3.6% [95% CI, −14.3% to 7.2%]; adjusted odds ratio, 0.93 [95% CI, 0.60-1.42]; P = .73). Of the serious adverse events, 5.0% (6 of 121 reported events) in the early tracheostomy group vs 3.4% (4 of 118 reported events) were related to tracheostomy.Among patients with severe stroke receiving mechanical ventilation, a strategy of early tracheostomy, compared with a standard approach to tracheostomy, did not significantly improve the rate of survival without severe disability at 6 months. However, the wide confidence intervals around the effect estimate may include a clinically important difference, so a clinically relevant benefit or harm from a strategy of early tracheostomy cannot be excluded.ClinicalTrials.gov Identifier: NCT02377167
Gesehen am 09.11.2022